Titanium mesh-supported TiO₂ nano-film for the photocatalytic degradation of ethylene under a UV-LED - Ji, Bang (2022)
In this paper, TiO2 nano-films with different morphologies were synthesized on titanium mesh by a hydrothermal treatment. The crystalline structure and surface morphology of the TiO2 nano-films were characterized by X-ray photoelectron spectroscopy (XRD), field emission scanning electron microscopy (FESEM), and high-resolution transmission electron microscope (HRTEM). The photocatalytic degradation of ethylene using the TiO2 catalyst was carried out. The effect of the photoreaction temperature, initial concentration of ethylene and light intensity on photodegradation under ultraviolet-light emitting diode (UV-LED) light was investigated. The photocatalytic stability of the TiO2 nano-film catalyst was also evaluated. The results revealed that the photodegradation of ethylene gas follows the pseudo-first-order kinetics model. The photoreactivity was enhanced by increasing the light intensity and the photoreaction temperature but decreased with the increase in the initial ethylene concentration. The nanowire-shaped TiO2 film showed a superior photocatalytic performance and an excellent stability. The electrochemical impedance spectroscopy and transient photocurrent response studies revealed that the nanowire-shaped TiO2 film possesses an excellent separation ability in the electron hole pair of the photogenerated electron-hole pairs due to the high degree of crystallinity and the heterojunction between the rutile and anatase phases of TiO2. We expect that the findings will have practical applications in fruit preservation and other agricultural products.